How divorced women can effectively enforce the financial support orders: the legal and administrative actions - Hasbullah@Abdullah, Muslihah; Mohd Zin, Najibah (Centre for Promoting Ideas (CPI), 2012)
The issue of inadequate enforcement of the financial supports order becomes an ongoing concern in Malaysia as well as in other countries. This paper aims to analyse the civil and criminal proceedings enforceable in the court of law against the defiance ex-husbands. Results of the content analysis revealed that the proper rules of civil and criminal procedure have been materialized to ensure the degree of impartiality in the administration of Islamic family law in Malaysia. On the other hand, the administrative machinery was found to have better enforcement power in tracking defaulters. Findings imply the need to boost up the legislative and administrative mechanisms to ensure effective execution of the financial supports order after divorce thus protecting the welfare of the divorced women. Comparative overviews with the practices from several Commonwealth and Middle East Countries where enforcement actions are in advance are also included